Building a global omni-channel commerce ecosystem: The Shopify story - GENG, Xuesong (Institutional Knowledge at Singapore Management University, 2022)
The case describes Shopify’s journey from a small online store to a global technology company with an ecosystem of partners that comprised of tens of thousands of developers and partners. From the inception of the company, Shopify’s competitive advantage had come from being merchant obsessed. Having an easy to set-up and easy to use technological platform, as well as a commercial model that leveraged an ecosystem of partners, had accelerated Shopify’s growth in building a merchant centric digital business. The case describes in detail the processes and drivers that had led to the success of Shopify. However, by 2022, competitive pressure from the other forms of commerce including live streaming commerce, social commerce and commerce from super apps had started to mount. Amazon, one of the world’s largest online marketplaces, had started to encroach on Shopify’s market by imitating its business model. The fusion of online and offline commerce had also driven Shopify to rethink its business model and the company started to shift its focus from eCommerce to general commerce. Shopify also wanted to penetrate the Southeast Asia (SEA) market further. High growth rates had been predicted for the region, but it was a heterogeneous market with lots of challenges including less than developed logistics infrastructure.